2006
DOI: 10.1007/s00167-006-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen on gene expressions of procollagen, matrix metalloproteinase and tissue inhibitor of metalloproteinase in injured medial collateral ligament and anterior cruciate ligament

Abstract: Animal experiments were performed to investigate whether and how the administration of hyperbaric oxygen (HBO) affects gene expressions of procollagens, matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in injured medial collateral ligament (MCL) and anterior cruciate ligament (ACL). In 64 Sprague-Dawley rats, the MCL of the left knee was lacerated at the midsubstance, and the ACL of the left knee was lacerated adjacent to the tibial insertion in another 64 rats. Of these, 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…It is interesting to note here that the duration of this antinociceptive effect (early-phase antinociception) is a multiple of the 90-min effect observed after a single HBO 2 exposure. This may suggest that HBO 2 treatment induces some type of up-regulation mechanism, which has been reported recently by others3,15,23.…”
Section: Discussionsupporting
confidence: 71%
“…It is interesting to note here that the duration of this antinociceptive effect (early-phase antinociception) is a multiple of the 90-min effect observed after a single HBO 2 exposure. This may suggest that HBO 2 treatment induces some type of up-regulation mechanism, which has been reported recently by others3,15,23.…”
Section: Discussionsupporting
confidence: 71%
“…Exposure of fibroblasts to 10 −9 M E 2 and 10 −7 M LY117018 tended to increase the amount of type III collagen and MMP-13 secreted in the culture medium and these effects of E 2 and LY117018 were attenuated by treatment with ICI 182,780 (10 −7 M). degradation [12], alterations in the expression of MMP-13 might indicate that estrogen deficiency retards collagen turnover and that treatment with either E 2 or SERM recovers MMP-13 expression to the premenopausal level. If this is the case in vivo, hormonal alterations after menopause might induce a breakdown in the balance of collagen metabolism and retard remodeling of the tendon ECM, leading to the degradation of tendon properties and structure.…”
Section: Discussionmentioning
confidence: 97%
“…Homeostasis of these tissues depends on the balance between 180 T. IRIE ET AL the synthetic and degradative activities of tendon fibroblasts [12]. The mechanical properties of these tissues change due to vascular, cellular, and collagen-related alterations, and the loss of elasticity and decrease in the strength of these tissues deteriorate motor function, leading to a decrease in the activities of daily living, especially in senile or postmenopausal people.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported an insufficient repair process and have tested different treatment regimens, including tissue engineering approaches, non-steroidal anti-inflammatory drugs, local corticosteroids, hyperbaric oxygen, growth factors, ultrasonic or electrical stimulation, laser therapy, and also gene therapy [Ng et al, 2004;Creighton et al, 2005;Chen et al, 2006;Chamberlain et al, 2009]. However, most of the experimental studies on animal models have focused on characterizing only the extracellular matrix in both normal and injured ligaments [Provenzano et al, 2001;Lo et al, 2002;Majima et al, 2006;Tashiro et al, 2006;Woo et al, 2006;Takeyama et al, 2007].…”
Section: Introductionmentioning
confidence: 99%